2021
DOI: 10.1002/tafs.10293
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multipiscivore Foraging Success on Native and Invasive Prey Fish under Variable Light Intensities

Abstract: Piscivorous fishes attack and consume a variety of prey; however, few studies have examined interactions of multiple predators with multiple prey species. The situational complexity of foraging at different times of day was explored by examining the interactions of paired native predators (Burbot Lota lota or Smallmouth Bass Micropterus dolomieu) with either native (Mottled Sculpin Cottus bairdii) or invasive (Round Goby Neogobius melanostomus) benthic prey. The study allowed the comparison of a pursuit predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 88 publications
(134 reference statements)
0
13
0
Order By: Relevance
“…However, extrapolation of these conclusions to other Ponto-Caspian gobies must be done with care. A similar experimental study conducted on the invasive Ponto-Caspian round goby N. melanostomus showed that the native predators, the burbot ( Lota lota ) and smallmouth bass Micropterus dolomieu , hunted the round goby less efficiently than a native cottid prey species, the mottled sculpin Cottus bairdii ( Michels et al 2021 ). One of the reasons for the discrepancy between the studies may be morphological differences between the gobiids ( Jakubčinová et al 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, extrapolation of these conclusions to other Ponto-Caspian gobies must be done with care. A similar experimental study conducted on the invasive Ponto-Caspian round goby N. melanostomus showed that the native predators, the burbot ( Lota lota ) and smallmouth bass Micropterus dolomieu , hunted the round goby less efficiently than a native cottid prey species, the mottled sculpin Cottus bairdii ( Michels et al 2021 ). One of the reasons for the discrepancy between the studies may be morphological differences between the gobiids ( Jakubčinová et al 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…Prey evasion success was calculated as the inverse probability of the predator locating, attacking, capturing and retaining prey (i.e. 1-P Reaction , Michels et al, 2021), using the approach identified for prey detection by predators (O'Brien, 1979;Keyler et al, 2015Keyler et al, , 2019Richmond et al, 2004). Descriptions of each stage are detailed in Michels et al (2021), but below are brief definitions.…”
Section: Evasion Successmentioning
confidence: 99%
“…1-P Reaction , Michels et al, 2021), using the approach identified for prey detection by predators (O'Brien, 1979;Keyler et al, 2015Keyler et al, , 2019Richmond et al, 2004). Descriptions of each stage are detailed in Michels et al (2021), but below are brief definitions. Reactions were defined as predators orienting towards moving prey (O'Brien, 1979).…”
Section: Evasion Successmentioning
confidence: 99%
See 2 more Smart Citations